The book of Acts as story a narrative-critical study - Bauer, David R. (Grand Rapids Baker Academic, 2021)
A senior New Testament scholar and teacher helps students understand the historical, literary, and theological issues of the book of Acts and introduces key concepts in the field of narrative criticism.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books